Effect of positive electrode modification on the performance of zinc-bromine redox flow batteries. (June 2020) - Archana, Kaliyaraj Selvakumar; Naresh, Raghu pandiyan; Enale, Harsha; Rajendran, Vinod; Mohan, A M Vinu; Bhaskar, Aiswarya; Ragupathy, P; Dixon, Ditty
Highlights: Graphite felt activated by thermal as well as plasma treatment Increase in surface area as well as functional group increases the performance of zinc-bromine flow battery Performance of the flow battery is dictated by the interaction of polybromide phase with the oxygen functional groups High amount of oxygen functional groups is beneficial especially for high current density cycling Abstract: Performance of the zinc-bromine redox flow battery is correlated to the surface properties of the positive electrode. Herein, we have modified the graphite felt electrode by thermal treatment and plasma treatment under oxygen and nitrogen atmospheres. These treatments induced specific changes to the electrode surface. Under the experimental conditions, thermal treatment increased overall surface area whereas, the O2 and N2 plasma increased the defects in the felt, by generating oxygen functional groups as well as N doping respectively. By combining both thermal and O2 plasma treatment, an increase in both surface area, as well as oxygen functional groups, were achieved. The performance of the cell was influenced by the surface area and surface functional groups. Most importantly surface oxygen functionalization proved to be a decisive factor for the enhanced performance especially when the concentration of organic polybromide phase is higher. A better charge transfer/adhesion between the electrode and polybromide phase is expected through halogen/hydrogen bonding between the complexed Br and oxygen/proton of the phenolic or carboxyl functional groups. Graphical abstract: Image, graphical abstract